Looking for a needle in a haystack: Call and advanced language proficiency - Burston, Jack; Arispe, Kelly (My University, 2018)
The goal of this meta-analysis is to evaluate how instructional technology has impacted advanced second language (AL2) development. Although numerous metaanalyses have been conducted within the CALL literature over the past two decades, they primarily focus upon learning outcomes and related effect sizes. None focuson advanced learning per se. Where AL2 is even mentioned, which is only rarely, little or no attention is paid to critical research parameters within the studies that are analyzed. Most notably, in summarizing learning outcomes, the linguistic competence of learners claimed to be at advanced level is simply taken at face value. So, too, no consideration is given to the difficulty level of tasks undertaken by students or their appropriateness to students’ claimed proficiency. It is the intent of this general overview of the contribution of CALL to AL2 to address these issuesthrough a comprehensive analysis of the publications in four prominent CALL journals(CALICO, CALL, Language Learning & Technology, and ReCALL) over some 30 years. In so doing, the Performance Descriptors (PD) and NCSSFL-Can-Do Statements (CDS) of the American Council on the Teaching of Foreign Languages (ACTFL) are adopted as external criteria for establishing student competence level, task difficulty, and appropriateness. This study concludes that not only are CALL AL2 studies extremely limited in number and focus, but also that they suffer from serious design flaws that call into question a great portion of the claims made regarding the contribution of instructional technology to the furthering of advanced-level foreign language competence.
Keywords: ACTFL; Advanced language; Instructional technology; Meta-analysis; Proficiency